#### Answer

\[{f^{,,}}\,\left( 0 \right) = 6\,\,\,and\,\,\,{f^{,,}}\,\left( 2 \right) = 6\]

#### Work Step by Step

\[\begin{gathered}
f\,\left( x \right) = 3{x^2} - 4x + 8 \hfill \\
Find\,\,the\,\,derivative\,\,of\,\,the\,\,function \hfill \\
{f^,}\,\left( x \right) = \,\,{\left[ {3{x^2} - 4x + 8} \right]^,} \hfill \\
Use\,\,the\,\,power\,\,rule \hfill \\
{f^,}\,\left( x \right) = \,\,3\,\left( 2 \right){x^{2 - 1}} - 4\,\left( 1 \right) \hfill \\
{f^,}\,\left( x \right) = \,\,6x - 4 \hfill \\
Find\,\,the\,\,\sec ond\,\,derivative \hfill \\
{f^{,,}}\,\left( x \right) = \,\,{\left[ {6x - 4} \right]^,} \hfill \\
{f^{,,}}\,\left( x \right) = 6 \hfill \\
Then \hfill \\
{f^{,,}}\,\left( 0 \right) = 6\,\,\,and\,\,\,{f^{,,}}\,\left( 2 \right) = 6 \hfill \\
\end{gathered} \]